Usability of free software used for visualization and measurement of digital orthodontic models (Bioscience Journal, 2021)
The aim of this study was to evaluate the usability of the free software available that allow visualization and measurement of orthodontic digital models. 80 graduate students of orthodontics were asked to perform pre-defined tasks in a digital model through 3D Viewer ® and 3D-Tool ® software. The success in accomplishing the tasks and the time spent were recorded. To end, each participant answered a questionnaire to express their satisfaction regarding the software. There were no statistically significant difference between the software when compared to the accomplishment rates of tasks and the time spent by participants on each one. The software were evaluated as "slightly satisfactory" in several criteria. There is scope for optimization of orthodontic software by manufacturers since lack of their interface usability can discourage orthodontists’ adherence to new resources that could provide benefits to their daily routine, even if they are freely available.